2016
DOI: 10.1051/epjconf/201611918005
|View full text |Cite
|
Sign up to set email alerts
|

Lidar Measurements of Canadian Forest Fire Smoke Episode Observed in July 2013 over Warsaw, Poland

Abstract: This paper presents a preliminary study of aerosol optical properties of air-mass advected on 10 th July 2013 from Canada above Warsaw, Poland, during the forest fire event that occurred in Quebec at the beginning of July 2013. The observations were conducted with use of the modern version of 8-channel Polly XT lidar capable of measuring at 3+2+2+VW and interpreted with available information from the MACC model, the CALIPSO and MODIS satellite sensors, the AERONET data products and the data gathered within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Mixtures of dust and pollution (brown/white squares in Fig. 2) have been observed at Évora (Preißler et al, 2013), Warsaw (Janicka et al, 2016(Janicka et al, , 2017, Nicosia (Kaduk, 2017) and while onboard the RV Meteor above the Atlantic Ocean (Rittmeister et al, 2017). The mean lidar ratios for this category are 48.5 ± 9.2 sr and 46.4 ± 8 sr, and particle linear depolarization ratios are 15.7 ± 1.7% and 17.7 ± 2.5% at 355 and 532 nm, respectively.…”
Section: Mixturesmentioning
confidence: 97%
See 1 more Smart Citation
“…Mixtures of dust and pollution (brown/white squares in Fig. 2) have been observed at Évora (Preißler et al, 2013), Warsaw (Janicka et al, 2016(Janicka et al, , 2017, Nicosia (Kaduk, 2017) and while onboard the RV Meteor above the Atlantic Ocean (Rittmeister et al, 2017). The mean lidar ratios for this category are 48.5 ± 9.2 sr and 46.4 ± 8 sr, and particle linear depolarization ratios are 15.7 ± 1.7% and 17.7 ± 2.5% at 355 and 532 nm, respectively.…”
Section: Mixturesmentioning
confidence: 97%
“…Smoke from Siberian wildfires, which was measured in the Arctic during the MOSAiC campaign, has also been added to the data collection (Ohneiser et al, 2021), which broadens even further the geographical coverage of the observations of that particular aerosol type. Smoke has been also observed above Europe frequently; from boreal forest fires in western Canada at Leipzig, Germany (Haarig et al, 2018), aged from Siberia/Canada measured at multiple EARLINET stations (Müller et al, 2007), long-range transported smoke from North America above Warsaw, Poland (Janicka et al, 2016(Janicka et al, , 2017 and fresh, locallyproduced smoke above Portugal (Pereira et al, 2014). The 355 nm mean lidar ratio and particle linear depolarization ratio are 68.2 ± 7.4 sr and 2.7 ± 1.3%, respectively.…”
Section: Smokementioning
confidence: 99%
“…optical properties of long-range transported volcanic ash during Eyjafjallajökull eruption in April 2010 were analyzed over Poland and Romania [2]. A recent study of the Canadian forest fire event observed over Warsaw during July 2013 revealed another air-mass path transporting mineral dust particles form Sahara [3]. Here we discuss a case of an air-mass flow from Poland to Romania, over the NW-SE transect that allows for assessing the role of Carpathian Mountains in this air-mass modification.…”
Section: Introductionmentioning
confidence: 99%